Enhancing High School Students’ Critical Thinking in Physics through a Virtual Classroom Critical Thinking Model: Supporting SDG 4 (Quality Education) - Tri Lestari (Postgraduate, University of Mataram, 2026)
Developing students’ critical thinking skills (CTS) has become an essential focus in 21st-century education, particularly in digital learning environments. This study aims to examine the effectiveness of the Virtual Classroom Critical Thinking (VC2T) model in enhancing senior high school students’ CTS in physics learning. A pre-experimental one-group pre-test–post-test design was employed involving 56 eleventh-grade students from two science classes at a private senior high school in Surabaya, Indonesia. Data were collected using a CTS test based on Facione’s indicators: interpretation, analysis, evaluation, inference, and explanation, and a student response questionnaire. Data analysis involved normalized gain (n-gain), paired-sample t-test, and effect size calculations. The results indicate a statistically significant improvement in students’ CTS after the implementation of the VC2T model, with a medium n-gain and strong effect size. In addition, students expressed positive response toward the VC2T-based learning experience. These findings suggest that the VC2T model has strong potential as an effective online instructional approach for fostering critical thinking skills in physics learning.